Accelerated MRI of the fetal heart using compressed sensing and metric optimized gating. Issue 6 (2nd June 2016) - Roy, Christopher W.; Seed, Mike; Macgowan, Christopher K.
Abstract : Purpose: To develop and validate a method for accelerated time‐resolved imaging of the fetal heart using a combination of compressed sensing (CS) and metric optimized gating (MOG). Theory and Methods: Joint optimization of CS and MOG reconstructions was used to suppress competing artifact from random undersampling and ungated cardiac motion. Retrospectively and prospectively undersampled adult and fetal data were used to validate the proposed reconstruction algorithm qualitatively based on visual assessment, and quantitatively based on reconstruction error, blur, and MOG timing error. Results: Excellent agreement was observed between the fully sampled and retrospectively undersampled reconstructions, up to an undersampling factor of four. Visually, differences between ECG and MOG reconstructions of adult data were negligible. This was consistent with quantitative comparisons of reconstruction error (RMSEECG  = 0.07–0.13; RMSEMOG  = 0.08–0.13), and image blur (BECG  = 1.03–1.20; BMOG  = 1.03–1.20). The calculated MOG timing error (2–42 ms) was comparable to the acquired temporal resolution (∼60 ms). Quantitative evaluation of retrospectively undersampled (R = 2–8) fetal data (RMSEMOG  = 0.06–0.12; BMOG  = 1.04–1.27) was comparable to the adult volunteer results. Conclusion: CS‐MOG for dynamic imaging of the fetal heart was developed and validated. Using CS‐MOG, images were obtained up to four times faster than conventional acquisitions. Magn Reson Med 77:2125–2135, 2017. © 2016 International Society for Magnetic Resonance in Medicine